Touch-bookmark: A lightweight navigation and bookmarking technique for E-books - Yoon, D.; Cho, Y.; Yeom, K.; Park, J.-H. (Conference on Human Factors in Computing Systems - Proceedings, 2011)
The navigation function of an e-book significantly influences its usability. In this paper, we introduce Touch-Bookmark (TB), a multitouch navigation technique for e-books. TB enables users to bookmark a page in a casual manner and return to it quickly when required. Moreover, the users can flip between two remote pages by using simple gestures. In a usability test conducted to evaluate our prototype, users found the technique easy to learn, natural to use, and useful for navigation. Analysis of the patterns of interaction gestures helped identify human factors that should be considered when designing touch interfaces for e-books. The factors include navigation strategies, patterns of interaction gestures, types of books, and motor memory.